SOLID BIOMASS GASIFICATION AND THE COST OF THE SYNGAS - Gherman C.; Shwets O.; Arseni L. (Problems of the Regional Energetics)
There has been determined the cost of syngas produced from straw and wood chips, for gasifiers of different capacities, under the conditions of the Republic of Moldova in this paper. The annual cost growth rates have been calculated. The levelized cost of syngas has been compared with the levelized cost of natural gas.